2014
DOI: 10.1002/cncr.28644
|View full text |Cite
|
Sign up to set email alerts
|

Children of cancer patients: Prevalence and predictors of emotional and behavioral problems

Abstract: BACKGROUND: Children of patients with cancer are at increased risk for developing emotional and behavioral problems. This study explored the prevalence and predictors of emotional and behavioral problems in children of cancer patients in a multisite research project. METHODS: A cross-sectional sample of N 5 235 families was recruited simultaneously in 5 university medical centers. The participants, including parents (N 5 402) and children (N 5 324; ages 11-21 years) completed standardized questionnaires. Emoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 30 publications
1
46
0
4
Order By: Relevance
“…Their distress is likely due to their vulnerability and reliance on positive family functioning [8,9] and concerns about the parent's survival and the family's future [7]. Distress can lead to emotional and psychosocial problems [6], such as problematic internalization (e.g., depressive mood states) or externalization (e.g., aggression, delinquency) of behavior [9,10].…”
Section: Introductionmentioning
confidence: 98%
“…Their distress is likely due to their vulnerability and reliance on positive family functioning [8,9] and concerns about the parent's survival and the family's future [7]. Distress can lead to emotional and psychosocial problems [6], such as problematic internalization (e.g., depressive mood states) or externalization (e.g., aggression, delinquency) of behavior [9,10].…”
Section: Introductionmentioning
confidence: 98%
“…Ill parents also reported significantly higher levels of internalising, externalising and total problems for their male children compared to the general population. Only in Möller and colleagues study (), both healthy and ill parents reported more emotional and behavioural problems in younger children than adolescents, independently from gender.…”
Section: Resultsmentioning
confidence: 83%
“…Eleven studies have shown that emotional and/or behavioural problems increased in most children and adolescents during their parent's illness (Compas, Worsham, Ey, & Howell, ; Compas et al., ; Costas‐Muñiz, ; Gazendam‐Donofrio et al., ; Grant & Compas, ; Krattenmacher et al., ; Küçükoĝlu & Çelebioĝlu, ; Möller et al., ; Thastum et al., ; Visser et al., ; Watson et al., ; Welch, Wadsworth, & Compas, ), while prevalence of social problems was more or less comparable to normative groups across studies. Percentages of clinically significant emotional and behavioural symptoms ranged from 7% (Möller et al., ) to 20% (Visser et al., ) in children under the age of 11, while in preadolescents and adolescents, the presence of symptoms ranged from 23% (Visser et al., ) to 30% (Edwards et al., ). Assumption of risky behaviours in adolescents ranged from 3% to 23% and was more or less comparable to scores in the normative group (Jantzer et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…36 Sevdikleri insanın ölümünü deneyimleyen kardeşlerde dürüst ve açık bir iletişim onu desteklemede önemlidir. 28,29,37,38,39 Yas sürecinde tüm yaştaki çocuklar, güven ortamı içinde, sü-reçle ilgili soru sorabilme ve paylaşımda bulunmaya gereksinim duyarlar. Ancak, bu gereksinim erişkinlerin çocukları olumsuz haberlerden koruma gerekçesi ile karşılanamamaktadır.…”
Section: Yas Sürecindeki çOcuğa Yardım Ve Hemşire-nin Rolüunclassified
“…Literatür ebeveynlerin bu konuda hemşireler tarafından desteklenmeleri gerektiğini belirtirken, 37,38,50,51 çoğu hemşire bu konuda eği-timlerinin yetersiz olması nedeniyle bu rehberliği sağlamada çekinik davranmaktadır. 39,42,43,49,51 Hemşireler ve ebeveynler, yas yaşayan çocukla iletişimde şunlara dikkat etmelidir: 1) Hasta kardeşin hastalığı ile ilgili bilgiler erken dönemde açık ve dürüst bir şekilde açıklanmalı-dır. 2) Kelimelerin yaratacağı etki unutulmamalı, bu nedenle kanser ve ölüm gibi kelimeler seçilirken dikkatli olunmalıdır.…”
unclassified